Experiences of caregivers on involvement in children's care at Mercy James Paediatric Intensive Care Unit in Blantyre, Malawi - Chasweka, Grace Glory (2021)
A child’s illness and admission in hospital is stressful and negatively affects the child, caregivers and the family. The stress is further exacerbated when a child is critically ill and has been admitted in an Intensive Care Unit. The effects can however be reduced when caregivers and families of the sick children are present and involved in the care of their hospitalized children. This practice is known as Family Centred Care (FCC) and it advocates that families should be involved in the care of their children. This was a descriptive study that used qualitative method to explore experiences of caregivers on their involvement in care at MJ PICU in Blantyre, Malawi. Data was collected from a purposive sample of ten caregivers who had been discharged from the PICU through in-depth interviews using a semi- structured interview guide. Qualitative data was analyzed using content analysis. The predetermined themes used were: caregivers’ experiences on their presence in PICU, information sharing by health workers to caregivers, participation in decision making and involvement in care activities. The study found several gaps as far as involvement of caregivers in the care of their children at MJ PICU is concerned. The information given to caregivers regarding their children’s care in the PICU was inadequate and was not standardized for caregivers to understand and adequately participate in their children’s care. Nurses and doctors were both found to have provided the information although ironically caregivers were unable to differentiate the two. The information was given verbally and in a language that the caregivers were able to understand. Caregivers were not adequately involved in decision making regarding their children’s care but were however involved in the physical care of their children. As such, it is recommended that specific interventions be developed to promote involvement of caregivers when they have been admitted with their children at MJ PICU.